Reformulating and Mirroring in Psychotherapy: A Conversation Analytic Perspective - Knol, A. S. L.; Huiskes, Mike; Koole, Tom; Meganck, Reitske; Loeys, Tom; Desmet, Mattias (Frontiers in Psychology, 2020)
The conversational actions of reformulating and mirroring constitute some of the core intervention techniques of psychotherapy. The purpose of the present study was to investigate the way in which therapists in cognitive-behavioral (CBT) and psychodynamic therapy (PDT) use reformulating and mirroring strategies to return patients’ prior talk and how their differential usage can be viewed in light of the respective manualized recommendations. A mixed methods approach was applied using qualitative data that derived from a RCT. The data collection consisted of 200 excerpts assembled from both treatment conditions. The method of Conversation Analysis was used to determine the practices that accomplished instances of reformulating and mirroring, and to examine their distinct implications for subsequent talk. The quantitative analysis revealed that cognitive-behavioral therapists are significantly more likely to use reformulations, which is in harmony with what is suggested in CBT’s treatment manuals. Psychodynamic therapists’ frequent use of transformative formulations is, by contrast, unexpected in regard to the suggestions of the treatment protocol, as these interventions steer toward topical closure. Compared to the CBT condition, psychodynamic therapists were still significantly more likely to rely on mirroring strategies, which are in line with PDT’s theoretical preference. Our findings raise the question whether alleged differences in treatment styles, as they are imposed by RCT methodology, are actually tangible in manual-guided clinical practice.